2020
DOI: 10.1108/jpif-10-2020-0119
|View full text |Cite
|
Sign up to set email alerts
|

Senior housing in Scotland: a development and investment opportunity?

Abstract: PurposeThis article aims to understand the housing needs of older people and to ascertain the level of demand and supply of age-related housing in Scotland. It also explores interest in different types of retirement accommodation and tenure options.Design/methodology/approachA review of existing literature is undertaken on senior housing preferences and residential satisfaction. Primary data is collected from an online survey of people over 55 in Scotland to ascertain demand side requirements with secondary da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…While for example, reference has been made by the Scottish government for the need to provide suitable housing for the elderly (Scottish Government, 2011), it has predominately been left to developers to react to the demand side signals and build appropriate dwellings. However, as there is an overall shortage of housing in Scotland, often developers see better profit margins in mainstream family housing and first-time buyer flats, thus discouraging senior housing opportunities, which require a different set of skills and expertise (Fyfe and Hutchison, 2021). The composition and motivations of the house-building industry is also worthy of investigation as the construction of senior housing is to a degree niche, which runs contrary to Encouraging the supply of senior housing the modus operandi of the volume house builders who are focussed on selling to a more generalist market.…”
Section: Literature Review 21 Neoliberalism and State Involvement In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…While for example, reference has been made by the Scottish government for the need to provide suitable housing for the elderly (Scottish Government, 2011), it has predominately been left to developers to react to the demand side signals and build appropriate dwellings. However, as there is an overall shortage of housing in Scotland, often developers see better profit margins in mainstream family housing and first-time buyer flats, thus discouraging senior housing opportunities, which require a different set of skills and expertise (Fyfe and Hutchison, 2021). The composition and motivations of the house-building industry is also worthy of investigation as the construction of senior housing is to a degree niche, which runs contrary to Encouraging the supply of senior housing the modus operandi of the volume house builders who are focussed on selling to a more generalist market.…”
Section: Literature Review 21 Neoliberalism and State Involvement In ...mentioning
confidence: 99%
“…of the population will be of pensionable age, compared to 19.0% in mid-2018 (Scottish Government, 2021a). The volume and type of housing required to support an ageing population is now under scrutiny, given that there is strong evidence that the current supply of senior housing, by both the private and public sector including housing associations, is insufficient to meet current demand (Fyfe and Hutchison, 2021). With demand levels for senior housing well established and understood, the challenge is more on the supply side and this paper will focus on the state's role in stimulating the supply of senior housing and more specifically, "housing-with-care".…”
mentioning
confidence: 99%
“…For instance, an institutional investor is likely to view BTR as a financial asset, but from the perspective of policymakers, it will be expected to generate social investment returns. The literature covers wide-ranging areas across different countries, including the understanding of the asset class, assessing its financial viability, examining government intervention models, and exploring the barriers [8,26,28,[56][57][58]. A more forward-thinking school of thought discusses it in the light of an affordable housing provision [30,[59][60][61].…”
Section: Build-to-rent: a Nexus For Affordable Housingmentioning
confidence: 99%
“…Numerous scholars have conducted investigations on the behavioural patterns exhibited by elderly individuals in order to understand the factors influencing their inclination towards relocating to CCRCs or senior housing facilities. In a recent study conducted by Fyfe and Hutchison (2020), it was observed that older individuals sought housing options throughout their retirement years, with a specific emphasis on factors such as the proximity to local amenities, ease of access to shopping facilities, establishment of social connections with neighbours, and the overall interior design of the residence.…”
Section: Senior Housing Industrymentioning
confidence: 99%